A Network Analysis Approach to Religious Commitment, Mental Health, and Well-Being of Indonesian Muslims - Purwandari, Eny; Priyadi, Suwanda; Taufik, Taufik; Handayani, Arifah; Calsum, Astri Yani; Azmi, Kenasty Sausan (Bulletin of Counseling and Psychotherapy, 2025)
Previous research has investigated how religious commitment relates to mental health and well-being through correlational studies and latent variable models. However, few studies have employed a network analysis approach to examine the reciprocal interactions among these variables. Consequently, this study utilizes network analysis to assess the connections between religious commitment, mental health, and well-being among Muslims in Indonesia, refers to data from the fifth Indonesia Family Life Survey (IFLS 5) carried out in 2014-2015. For our analysis, we focused on the Muslim population and included only those who identified as Muslim. With this criteria, we obtained a total sample of 28,392 individuals. EBICglasso network model display node religiosity (religious commitment) had a direct negative association with restless (mental health problem), effort (mental health problem), and trouble (mental health problem) and had a direct positive association with life satisfaction (well-being), happiness (well-being), and lonely (mental health problem). on the other hand, node prayer (religious commitment) had a direct negative association with lonely (mental health problem) and had a direct positive association with economic status (well-being), health status (well-being), and fearful (mental health problem). Nodes pengajian (religious commitment) had a direct negative association with trouble (mental health problem) and had a direct positive association with effort (mental health problem), and could not (mental health problem). In conclusion, a bidirectional influence between religious commitment, mental health and well-being should be considered.